2009
DOI: 10.1074/jbc.m109.005694
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Exploitation of Inhibitor-resistant Aurora and Polo Kinase Mutants for the Analysis of Mitotic Networks

Abstract: The Aurora and Polo-like kinases are central components of mitotic signaling pathways, and recent evidence suggests that substantial cross-talk exists between Aurora A and Plk1. In addition to their validation as novel anticancer agents, small molecule kinase inhibitors are increasingly important tools to help dissect clinically relevant protein phosphorylation networks. However, one major problem associated with kinase inhibitors is their promiscuity toward "off-target" members of the kinome, which makes inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 65 publications
6
100
1
Order By: Relevance
“…Resistance to PLK1 inhibition might also be due to mutations in the ATP-binding site of PLK1. Scutt and colleagues (24) found that mutation of Arg136 to Gly in the PLK1 ATPbinding pocket could alter the sensitivity to PLK1 inhibitors in a compound-specific manner. Further efforts will be required to define potential patient stratification factors to help identify the tumors most vulnerable to TAK-960 and to determine whether combinatorial approaches may lead to durable tumor regression.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to PLK1 inhibition might also be due to mutations in the ATP-binding site of PLK1. Scutt and colleagues (24) found that mutation of Arg136 to Gly in the PLK1 ATPbinding pocket could alter the sensitivity to PLK1 inhibitors in a compound-specific manner. Further efforts will be required to define potential patient stratification factors to help identify the tumors most vulnerable to TAK-960 and to determine whether combinatorial approaches may lead to durable tumor regression.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometric assay showed that after incubation with LRD-22 at indicated concentrations for 24 h, the percentage of apoptotic HepG2 cells increased from 6.71% in the control group to 15.11% in the group treated with 8 mM LRD-22 (Fig. S2).…”
Section: Lrd-22 Induces Hepg2 Cell Apoptosismentioning
confidence: 92%
“…Activation of AURKA requires binding to specific cofactors including Ajuba, Bora and TPX2, leading to the autophosphorylation of a residue in its T-loop (Thr 288 ) [15]. Its kinase activity increases from late G2-phase onwards and peaks in prometaphase.…”
Section: Introductionmentioning
confidence: 99%
“…Immunofluorescence microscopy images show that centrosomal Aurora-A is strongly phosphorylated, whereas Aurora-A bound to TPX2 to spindle microtubules is weakly phosphorylated [16,17]. It would appear that, at the centrosome, Aurora-A is primarily activated by phosphorylation, whereas on the mitotic spindle the action of PP6 (protein phosphatase 6) (the cellular phosphatase for Aurora-A [18]) keeps Aurora-A in a mainly dephosphorylated state and ensures that activation is primarily via TPX2 binding.…”
Section: Aurora-a: Activation By Phosphorylation and Protein Partner mentioning
confidence: 93%